Foreign Emigration of Young Nurses from Socio-Economically Disadvantaged Regions. The Example of Nursing Students from The Main Academic Centres of Eastern Poland - Grazyna KOWALEWSKA (Communications of International Proceedings, 2024)
The aim of the research was to determine the tendency to emigrate nursing students from socio-economically weak regions. Additionally, the goals of trips abroad and the family's influence on students' migration plans were identified. The TOPSI method was used to identify voivodeships with the worst socio-economic situation, and the original research survey was the tool for verifying the set goals and hypotheses. The study covered five voivodeships of Eastern Poland (Warmińsko-Mazurskie, Podlaskie, Świętokrzyskie, Lubelskie and Podkarpackie). The study was conducted among nursing students at 5 major academic centers. 745 completed surveys were received. The conducted own research shows that voivodeships of Eastern Poland are characterized by a weak economic and social situation. A low income encourages people to go abroad to work, especially as it is possible to earn several times more there. For most of respondents, their relatives had a strong influence on their migration decisions. Another important aspect of economic emigration was the desire to help family remaining in the country. The majority of respondents indicated that the purpose of their departure was to work abroad.
Keywords: migration; students; nurses.